Implementation of Anti Corruption Educational Values in Civic Education Lessons at Elementary Schools in Nuhon Subdistrict, Banggai Regency - Muh. Taufik Poito; Udin Hamim; Muchtar Ahmad (FKIP - Universitas Riau, 2026)
Corruption remains an issue that reflects the weakening of moral values and integrity in society, thus requiring preventive efforts through education. This study aims to analyze the implementation of anti-corruption educational values in Civic Education lessons at elementary schools in Nuhon Subdistrict, Banggai Regency. The study employs a qualitative descriptive approach to understand the process of value internalization in learning. Data were collected through in-depth interviews, non-participant observation, and documentation involving school principals, teachers, and sixth-grade students. The results indicate that the values of honesty, responsibility, and discipline are applied through integration into the curriculum, the routine practice of activities, teacher modeling, and reinforcement through school culture. This approach enables students not only to understand these values conceptually but also to incorporate them into their daily lives. Unlike previous studies, which tended to be conceptual and focused on higher levels of education, this study highlights actual practices in elementary schools in Nuhon Subdistrict, an area that has been rarely studied. This study confirms that anti-corruption education is more effective when implemented in an integrated manner across learning, behavior, and the school environment.